SUPPLY CHAIN MANAGEMENT IN FINNISH RETAILING COMPARISON TO WORLD CLASS COMPANY CASE SEVEN ELEVEN JAPAN.CO AND WALMART - Widia Febriana; Juliana Palit; Defel Septia Septian (The Journal Publishing, 2020)
Lee titled The Triple A Supply Chain. In the article Lee picks up one world-class company that has excelled in designing its supply chain to meet the three points that make supply chains effective according to Lee. Those three are the long and short time flexibility and interest group commitment. The purpose of this research was to find out how the supply chains of Japanese and Finnish retail companies are different or similar to each other, how can Finnish retail companies improve their supply chains, and what kind of electronic tools are used in retail supply chains. The scope of the study was limited to the supply chains of grocery retail business in Finland and Japan and in particular Seven Eleven Japan and Walmart. The current situation of the grocery retail industry in Finland and Japan and the main trends of the grocery retail markets in both countries were described. Seven-Eleven Japan has developed an extensive franchise network and performs a key role in the daily operations of this network.